Appraisal of transport infrastructure for pedestrians in the city area, the case of Pardubice. - Bulícek, Josef; Bro ová, Pavlína (Palacký University, 2017)
The paper is focused on pedestrian traffic in city area of Pardubice. Three localities are characterized in the first part of the paper. Each of them is illustrating one different problem of pedestrian transport. The first locality is a rush interchanging node of urban public transport located on both sides of a rush street. Problems related to passengers crossing this street by interchanging are highlighted. The second locality is representing a problem of decision between pedestrian level crossing or underpass. The third locality is representing a place with complicated interaction between transport participants (pedestrians and cyclists) in the case of limited spatial conditions. Unintuitive using of traffic marking and traffic signs is also mentioned. Proposed measures for improving of conditions in pedestrian transport are mentioned in local as well as general points of view. Second part of the paper is focused on conditions for pedestrians along one of the most frequented pedestrian routes in Pardubice. This route is connecting the main railway station and the city center (Pern týnské Square). Pedestrian crossings and individual segments of this route are considered independently. Presented appraisal can be used as a theoretical base (example-based) for appraising of other pedestrian routes as well. Possible measures for improving of conditions in pedestrian transport are mentioned in the paper as well.
Keywords: Fußgängerverkehr; Individualverkehr; Straßenverkehr; Infrastruktur; Verkehrssicherheit; Fußgänger; Unterführung; Stadtgebiet